Intermittent Fasting to the Eye: A New Dimension Involved in Physiological and Pathological Changes - Feng, Jiaqing; Zhang, Shijiao; Li, Wenning; Bai, Tianle; Liu, Yulin; Chang, Xingyu (Frontiers in Medicine, 2022)
Intermittent fasting (IF) is gaining popularity as a therapeutic dietary strategy that regulates metabolism and can alter the development of metabolic disorders. An increasing amount of research has connected ocular diseases to IF and discovered that it has a direct and indirect effect on the eye’s physiological structure and pathological alterations. This article summarizes the progress of research on IF in regulating the physiological structures of the ocular vasculature, the anterior segment of the eye, the retina, and the choroid. We explored the therapeutic potential of IF for various common ocular diseases. In the future, a comprehensive study into the fundamental processes of IF will provide a direct and rigorous approach to eye disease prevention and therapy.